What knowledge and attitudes do paid carers of people with a learning disability have about cancer?. (26th December 2012) - Wyatt, D.; Talbot, P.
What knowledge and attitudes do paid carers of people with a learning disability have about cancer? The purpose of this study was to explore the knowledge and attitudes of paid carers of people with a learning disability regarding cancer. A questionnaire was utilised to gather information from carers involved in the social care of adults with learning disabilities within the independent sector. A total of 324 questionnaires were returned. Subjects were asked to provide words that they associated with cancer to provide data on their attitude to cancer. Knowledge‐based questions examined their knowledge on the possibility of recovery from cancer, the likelihood of cancer (particularly in relation to people with learning disabilities), types of cancer, risk reduction and early signs and detection. Subjects were also asked for their views regarding the adequacy of their knowledge and training needs. The findings indicated that the carers had some knowledge regarding cancer, but strategies for preventing and detecting cancer with adults with learning disabilities were not clearly elucidated.